2013
DOI: 10.1007/s10616-013-9536-8
|View full text |Cite
|
Sign up to set email alerts
|

Daphnoretin-induced apoptosis in HeLa cells: a possible mitochondria-dependent pathway

Abstract: Daphnoretin is a bicoumarin compound isolated from a natural product, Wikstroemia indica, which has been used to treat many diseases. It has strong antiviral and anti-tumor activities. Taking the anti-tumor activity of daphnoretin as a starting point, the present study aimed to test the pro-apoptotic effect of daphnoretin and its underlying mechanism in HeLa cells. The inhibitory effects of daphnoretin on viability and proliferation of HeLa cells were determined by the MTT assay. Daphnoretin-induced apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…( 16 ) as well as Daphne mezereum L. and Daphne cannabina Wall. ( 17 ), have been shown to induce cell cycle arrest and apoptosis in leukemia, osteosarcoma and HeLa cells ( 13 15 ). These findings suggest that daphnoretin may have potential as a novel anti-cancer agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 16 ) as well as Daphne mezereum L. and Daphne cannabina Wall. ( 17 ), have been shown to induce cell cycle arrest and apoptosis in leukemia, osteosarcoma and HeLa cells ( 13 15 ). These findings suggest that daphnoretin may have potential as a novel anti-cancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that daphnoretin has a number of biological activities, including antifungal effects ( 8 ), as well as the inhibition of various sites involved in DNA synthesis ( 9 ), the activation of protein kinase C in platelet aggregation ( 7 , 10 ), an antiviral effect on hepatitis B ( 11 ) and respiratory syncytial virus properties ( 12 ). Furthermore, the anticancer effect of daphnoretin has been reported in various studies ( 13 15 ). Such studies have shown that daphnoretin exerts its anticancer effects through the inhibition of cancer cell proliferation, the induction of G 2 /M-phase arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…A study demonstrated that daphnoretin induced apoptosis in human osteosarcoma cells by triggering G 2 /M cell cycle arrest and activating the caspase-3 pathway (21). In another study, daphnoretin was shown to induce the mitochondria-mediated apoptosis of HeLa cells (22). Daphnoretin has also been reported to influence the proliferation and apoptosis of A549 lung cancer cells in vitro (23).…”
Section: Daphnoretin Exerts Antitumor Effects In Specific Tumor Typesmentioning
confidence: 99%
“…Unlike other cell lines, one of the characteristics of HeLa cells is their abnormally rapid proliferation rate. Hela cells can adapt to different growth conditions and different cell culture media, such as DMEM, MEM, RMPI1640, DMEM/F12K, and are very easy to culture. Therefore, HeLa cells are one of the most important sources of cell cross‐contamination.…”
Section: Introductionmentioning
confidence: 99%